2020
DOI: 10.1152/japplphysiol.00376.2020
|View full text |Cite
|
Sign up to set email alerts
|

Variations in loop gain and arousal threshold during NREM sleep are affected by time of day over a 24-hour period in participants with obstructive sleep apnea

Abstract: We investigated if time of day affects loop gain and the arousal threshold during non-rapid eye movement (NREM) sleep. Eleven males with obstructive sleep apnea completed a constant routine protocol comprised of sessions in the evening [10 PM (1) to 1 AM], morning (6 AM to 9 AM), afternoon (2 PM to 5 PM) and subsequent evening [10 PM (2) to 1 AM]. During each sleep session loop gain and the arousal threshold was measured during NREM sleep using a model-based approach. Loop gain and the arousal threshold were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This may be the case because the hypoxic ventilatory response is lower in the evening compared to other times of the day, at least in individuals with obstructive sleep apnea ( Gerst III et al, 2011 ). In support of this notion, it has been shown that chemoreflex sensitivity and loop gain (which is impacted in part by modifications in chemoreflex sensitivity) during sleep is lower in the evening compared to the morning and afternoon in individuals with obstructive sleep apnea ( El-Chami et al, 2014 ; Puri et al, 2020 ). Given these findings, there might be a greater range available for the hypoxic ventilatory response to increase during exposure to intermittent hypoxia.…”
Section: Factors That Impact the Magnitude Of Respiratory Plasticitymentioning
confidence: 92%
See 1 more Smart Citation
“…This may be the case because the hypoxic ventilatory response is lower in the evening compared to other times of the day, at least in individuals with obstructive sleep apnea ( Gerst III et al, 2011 ). In support of this notion, it has been shown that chemoreflex sensitivity and loop gain (which is impacted in part by modifications in chemoreflex sensitivity) during sleep is lower in the evening compared to the morning and afternoon in individuals with obstructive sleep apnea ( El-Chami et al, 2014 ; Puri et al, 2020 ). Given these findings, there might be a greater range available for the hypoxic ventilatory response to increase during exposure to intermittent hypoxia.…”
Section: Factors That Impact the Magnitude Of Respiratory Plasticitymentioning
confidence: 92%
“…More importantly for the present review, measures of oxidative stress are correlated to loop gain ( Panza et al, 2019 ) in humans. Loop gain is in part impacted by the sensitivity of the response to hypoxia ( Puri et al, 2020 ). Likewise, increases in oxidative stress induced by repeated daily exposure to intermittent hypoxia were positively correlated to increases in the ventilatory response to hypoxia that occurred following 4 days of exposure to intermittent hypoxia ( Pialoux et al, 2009 ).…”
Section: Progressive Augmentation Of the Hypoxic Ventilatory Responsementioning
confidence: 99%
“…Circadian rhythms could also play a role in OSA (von Allmen et al, 2018) and comorbid insomnia and OSA (COMISA) (Sweetman et al, 2021). Effects of circadian rhythms on respiratory control (Stephenson, 2003;Yamauchi et al, 2014) and hypoxia (von Allmen et al, 2018) have also been hypothesized and supported by recent evidence of circadian modulation of the key OSA endotypes (El-Chami et al, 2014Puri et al, 2020). Circadian rhythms also have an influential effect on metabolism, diabetes, cardiovascular disorders, obesity, and the efficacy of a range of pharmacological interventions; factors often applicable to sleep disorder cohorts (Guo and Stein, 2003;Frazier and Chang, 2020;Ayyar and Sukumaran, 2021).…”
Section: Circadian Rhythmsmentioning
confidence: 99%
“…An unstable ventilatory control system is characterized by a loop gain value greater than one. Controller gain is altered by modifications in chemoreflex sensitivity [ 26 ]. The greater the ventilatory response to a given level of hypoxia or hypercapnia, the greater the controller gain.…”
Section: Aging Women Loop Gain and Obstructive Sleep Apneamentioning
confidence: 99%